Antibody-Drug Conjugates: The Last Decade - Nicolas Joubert; Alain Beck; Charles Dumontet; Caroline Denevault-Sabourin (MDPI AG, 2020)
An armed antibody (antibody-drug conjugate or ADC) is a vectorized chemotherapy, which results from the grafting of a cytotoxic agent onto a monoclonal antibody via a judiciously constructed spacer arm. ADCs have made considerable progress in 10 years. While in 2009 only gemtuzumab ozogamicin (Mylotarg®) was used clinically, in 2020, 9 Food and Drug Administration (FDA)-approved ADCs are available, and more than 80 others are in active clinical studies. This review will focus on FDA-approved and late-stage ADCs, their limitations including their toxicity and associated resistance mechanisms, as well as new emerging strategies to address these issues and attempt to widen their therapeutic window. Finally, we will discuss their combination with conventional chemotherapy or checkpoint inhibitors, and their design for applications beyond oncology, to make ADCs the magic bullet that Paul Ehrlich dreamed of.